2009
DOI: 10.2139/ssrn.1496317
|View full text |Cite
|
Sign up to set email alerts
|

20 Years of German Unification: Evidence on Income Convergence and Heterogeneity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The median wage gap, for instance, was 5.7 percentage points larger in 2010 than in 1996. A similar pattern of divergence during the 2000s has been reported by Brück and Peters () for household income.…”
Section: Resultssupporting
confidence: 85%
“…The median wage gap, for instance, was 5.7 percentage points larger in 2010 than in 1996. A similar pattern of divergence during the 2000s has been reported by Brück and Peters () for household income.…”
Section: Resultssupporting
confidence: 85%
“…Thus, independent of socialisation or adaptation effects, migrants' behaviour patterns may be expected to differ from those of non-migrants at their place of origin. East-west German migrants have been found to be selected by sex, age, education, level of qualification, and partnership and parental status (Brück and Peters 2009;Büchel and Schwarze 1994;Gernandt and Pfeiffer 2008;Hunt 2000;Schneider et al 2008). 7 In addition, eastern German women have been shown to have a stronger work orientation than western German women and to be less inclined to adopt the male breadwinner model (Adler 2004).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…7 In addition, eastern German women have been shown to have a stronger work orientation than western German women and to be less inclined to adopt the male breadwinner model (Adler 2004). Migrants are also likely to have a strong employment orientation (Brücker and Trübswetter 2004;Melzer 2013), as they mainly migrate for employment and education reasons (Brück and Peters 2009;Büchel and Schwarze 1994;Fuchs-Schündeln and Schündeln 2009;Hunt 2000;Schneider et al 2008). The relationship between fertility and migration is chiefly influenced by the motivation for migration, with employment reasons being associated with reduced fertility propensities (Castro Martin and RoseroBixby 2011; Mussino and Strozza 2012;Nedoluzhko and Andersson 2007).…”
Section: Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…In their seminal work, Barro and Sala-i-Martin (1991) found unconditional convergence between states of the United States [11]. Further studies also found evidence of unconditional convergence mostly in developed countries, including Canada [19], Australia [16], Spain [24], Germany during reunification [15] and Indonesia [41]. Other studies, mostly in less developed countries, found little evidence of convergence including Italy [50], Russia [29], China [32], Mexico [7], and Colombia [14,45].…”
Section: Introductionmentioning
confidence: 99%